Litter Decomposition Pattern in Fraxinus excelsior and Ulmus villosa Forests in Different Seasons in Dachigam National Park, J&K, India - Bhat, Nisar; Reshi, Zafar; Verma, Raj Kumar; Malik, A. R. (Indian Forester, 2009)
The present study was to determine the decomposition pattern of litter of Fraxinus excelsior and Ulmus villosa forests in different seasons in Dachigam National Park, Srinagar, Jammu and Kashmir. The pattern of litter decomposition seems to have been more by presence of micro organisms and favourable climatic conditions. There was about 22.7 gm weight loss in F. excelsior and 20.78gm in U. villosa with in 12 months of decomposition. 95% exponential rate of decomposition was 2.04 and 2.55 indicating faster decomposition in F. excelsior as compared to U. villosa.